Uncertainty is Change - Kai Carstensen; Rüdiger Bachmann; Martin Schneider; Stefan Lautenbacher (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper provides survey evidence on firms' subjective uncertainty about future sales growth from a new representative panel data set of the German manufacturing sector. The main finding is that uncertainty reflects change: firms report more subjective uncertainty after either high or low growth realizations. In the cross section of firms, subjective uncertainty differs from statistical measures of uncertainty such as volatility: fast-growing and large firms report lower subjective uncertainty than fast-shrinking and small firms, respectively, even if they face shocks of similar size. In contrast, the substantial time variation in firm-specific subjective uncertainty resembles that in conditional volatility: both measures of uncertainty are mildly persistent and rise more when growth is temporarily low.
Keywords: C83; D22; E23; C83; D22; E23; 330; expectation formation; firms; measurement; subjective uncertainty; survey data